وەبەرهێنانی وەبەرهێنەرانی دەوڵەتی تورکیا لە هەرێمی کوردستان (توێژینەوەیەک لە جوگرافیای ڕامیاریدا) - کەریم, پ.ی.د ئەحمەد ڕەفیق; محەمەد, صباح لطيف (Sulaimani Journal for Humanities, 2023)
Kurdistan Regional Government issued investment law in 2006, caused logical investment and paved the way for foreign investment, this made countries to invest in Kurdistan. Turkish Republic is the most investor in Kurdistan during the years 2009-2015, all invested projects are )16( the the amount of invested capital was (1,232,716,673) dollars, and with Iraqi Government invested )6( projects during the years (2008-2016), the amount of invested capital was (251,450,520) dollars, the most of these projects of both types in 2011, and the most capital used in 2012. This research is to show generally the size of investment in the Kurdistan Region, and partically Turkish investment. The importance of this research is that it is a new topic and enrolling on this issue is least, it based on the descriptive method of the topics discussed. Finally the Turkish State has played a major role in the reconstruction of the Kurdistan Region, although most of the advantage of Kurdistan Region went to Turkish investors and the Turkish State. Keywords: Investment, Types of investment, Company, Turkish State, Kurdistan Region.